An In Vivo Study of Lactobacillus rhamnosus (PTCC 1637) as a New Therapeutic Candidate in Esophageal Cancer. (24th June 2022) - Hashemi-Khah, Malihe-sadat; Arbab-Soleimani, Nazila; Forghanifard, Mohammad-Mahdi; Gholami, Omid; Taheri, Saba; Amoueian, Sakineh
Abstract : Statement of Novelty . Esophageal cancer is one of the most common types of cancer globally. Nowadays, Lactobacilli with probiotic potency is a preventing factor in cancer and many diseases. The anti-tumor properties of these bacteria have been indicated in various studies. Objective . This study is aimed at investigating the effect of probiotic Lactobacillus rhamnosus on esophageal cancer in vivo and in vitro . Methods and Results . In this study, the cytotoxicity effects of L. rhamnosus supernatant and whole-cell culture on a cancer cell line (Kyse30) compared to 5fu were evaluated by the MTT assay. The real-time PCR method was used to analyse the L. rhamnosus supernatant effect on the expression of Wnt signaling pathway genes. An in vivo investigation in nude mice was done to assess the anti-tumor activity of L. rhamnosus supernatant and whole-cell culture. Both supernatant and whole-cell culture of L. rhamnosus reduced cell survival (Kyse30) P < 0.001 . The supernatant of this bacterium significantly reduced the expression of Wnt signaling pathway genes. Administration of supernatant and whole-cell culture of L. rhamnosus expressively reduced tumor growth compared to the control group. The effects of this bacterium on tumor necrosis were quite evident, pathologically P < 0.01 . Conclusion . This study is the first report that assessed the potential impact of L. rhamnosus, especially its supernatant on esophageal cancer and Wnt signaling pathway genes. Therefore, this bacterium can be a harmless candidate for esophageal cancer therapy.